A charter for women, 2006 (2006)
2006 1960-2000 "A charter for women, 2006" [EP0168], 2006 The RMT Women's Charter was issued by the National Union of Rail , Maritime and Transport Workers in 2006. Issues covered include equal pay and conditions, sexual harassment, menopause, health and safety, maternity care, childcare, hours and uniforms. The cover picture is 'Rosie the Riveter', an iconic image of U.S. women workers during the Second World War.